A randomized controlled trial of The Body Project: More Than Muscles for men with body dissatisfaction. Issue 8 (8th May 2017) - Brown, Tiffany A.; Forney, K. Jean; Pinner, Dennis; Keel, Pamela K.
Abstract: Objective: Pressures for men to conform to a lean, muscular ideal have, in part, contributed to eating disorder and muscle dysmorphia symptoms, yet few programs have been developed and empirically evaluated to help men. This study investigated the acceptability and efficacy of a cognitive dissonance‐based (DB) intervention in reducing eating disorder and muscle dysmorphia risk factors in men with body dissatisfaction. Method: Men were randomized to a two‐session DB intervention ( n = 52) or a waitlist control condition ( n = 60). Participants completed validated measures assessing eating disorder risk factors preintervention, postintervention, and at 1‐month follow‐up. Results: Program ratings indicated high acceptability. The DB condition demonstrated greater decreases in body‐ideal internalization, dietary restraint, bulimic symptoms, drive for muscularity, and muscle dysmorphia symptoms compared with controls ( p values < .02; between‐condition Cohen's d = .30–1.11) from pre‐ to postintervention. At one‐month follow‐up, the DB condition demonstrated significantly lower scores for all variables ( p values < .03; between‐condition d = .29–1.16). Body‐ideal internalization mediated intervention outcomes on bulimic and muscle dysmorphia symptoms. Discussion: Results support the acceptability and efficacy of The Body Project: More Than Muscles up to 1‐month postintervention and should be examined against active control conditions.